Children Learning to Code : Essential for 21st Century Human Capital - World Bank (World Bank, Washington, DC, 2019)
This book explores the premise that coding is an essential 21st century skill required for all. Learning of coding does not merely mean learn the syntax, grammar and usage of a specific computer language like Python or Ruby, but the deeper concept of computational thinking. It is possible to learn aspects of computational thinking without learning coding, but coding is essential to acquire a sound understanding and knowledge of computational thinking. The book is intended to be helpful to policy makers at the Federal and Regional level who are concerned about the need for the Russian Education system to be responsive to the demands that will be faced by children growing up today into a networked, connected world of ever-increasing digitization and online and offline collaboration. The book will also be helpful to teachers and parents and other adults who are interested in understanding more about the subject of preparing children for the 21st century from both theoretical and practical perspectives. It is also useful to explain what this book is not, even though it refers to a substantive body of rich and growing academic work on the subject, it is not intended to be an academic work that would contribute new knowledge. Most of this academic work does not appear in headlines or social media feeds of non-specialists, but quite a bit of the work is very interesting and relevant. This book has tried to translate some of this knowledge in understandable terms to policy makers and practitioners, without oversimplifying complex realities. An extensive set of references including website urls will allow the interested reader to delve deeper into any of the topics.